Pendidikan Tinggi Islam Dan Peradaban Indonesia - Hasbi Indra (AL-TAHRIR, 2016)
Abstract: Indonesia’s Islamic higher education has a strategic position in developing the future of Indonesian civilization. The institution which was established in the era of independence has been as a part of Indonesia education system following the policies and regulations made by the government. Pendidikan tinggi Islam mengalami dinamika dan pengembangan antara lain dari STAIN/IAIN (Sekolah Tinggi Agama Islam Negeri/Institut Agama Islam Negeri) menjadi UIN (Universitas Islam Negeri).  The Islamic High Education has been experiencing dynamical changes and developments which started from Sekolah Tinggi Agama Islam Negeri/ Institute Agama Islam Negeri (STAIN/IAIN) which are then changed into Universitas Agama Islam Negeri (UIN). In addition, private Islamic high school and private Islamic university have also developed. And their existence continues to develop up to this era of globalization. The globalization era is indicated by the massive development of sciences and technology creating a borderless world where people can communicate each other easily in a distance places.  . This globalization era is also marked by an open economy with its system of capitalism that has brought human being to easily fulfill their sexual libido. Now days, Islamic high education also exists amid international trades, including bilateral trade among Asian countries that should be responded in order to produce qualified graduates. Although the role of Islamic High Education has not given an optimal contribution to the nation, this research attempts to describe its existence and history since its birth in independence. With all of its potentials it has, Islamic High Education provides human resources in all aspects of life. It is not impossible for Islamic high education, as a part of nation, to bring Indonesia to reach its civilization peak. Like the civilization that had happened several decades ago, that is, in the era of the Umayyad and the Abbasid, was a good example of Islamic golden era that should be achieved back.  الملخص: كان التعليم العالي الإسلامي الإندونيسي مصدرا مهمّا في تكوين الحضارة الإندونيسية في المستقبل. وأصبح هذا التعليم العالي الإسلامي – القائم  منذ بداية عهد استقلال إندونيسيا – كقسم من أقسام النظام التربوي الإندونيسي عبر الأنظمة والقوانين التي قررتها الحكومة، ثم تطوّر من اسم STAIN/IAIN  إلى أن يكون باسم الجامعة الإسلامية الحكومية UIN. وبجانب ذلك وتطوّر كذلك STAIS  و  UIS.  وكان التعليم العالي الإسلامي تطوّر في عصر العولمة هذا. واتّسم عصر العولمة بتطوّر العلوم والتكنولوجيا وأدت العولمة إلى انفتاح الحياة البشرية للاتصال بأناس آخرين في الأماكن الأخرى البعيدة. وتتّسم العولمة كذلك بالإقتصاد المتفتّح التابع للنظام الرأسمالي الذي يؤدّى إلى أن يكون الناس أحرارا في الأداء الجنسي. وكان التعليم العالي الإسلامي في وسط التجارة العالمية وفيها العلاقات الاقتصادية بين الدول في آسيا التي لابد من الاهتمام بها ليُخرّج التعليم العالي الإسلامي الخرّيجين المتفوّقين. حاولت هذه الدراسة عرض التعليم العالي بتاريخه الطويل ومنذ نشأته في بداية عهد الاستقلال الإندونيسي، إلا أن دوره في الشعب الإندونيسي لم يكن فعّالا. وبما لدى التعليم العالي الإسلامي من الامكانات والطاقات أعدّ هو الموارد البشرية في جميع نواحي الحياة، ولا يستحيل أن يكون هو قسما من هذا الشعب ليحمله إلى حضارته كالحضارة التي وصل إليها المسلمون في عهد خلافة بني أمية وبني عبّاسية.  Abstrak: Pendidikan Tinggi Islam Indonesia merupakan wahana yang penting dalam pembentukan peradaban Indonesia masa depan. Lembaga yang didirikan sejak awal kemerdekaan ini telah menjadi bagian dari sistem pendidikan nasional melalui peraturan dan perundangan yang dibuat oleh pemerintah. Pendidikan tinggi Islam mengalami dinamika dan pengembangan antara lain dari STAIN/IAIN (Sekolah Tinggi Agama Islam Negeri/Institut Agama Islam Negeri) menjadi UIN (Universitas Islam Negeri). Juga berkembang Sekolah Tinggi Islam Swasta (STAIS) dan Universitas Islam Negeri (UIS). Eksistensinya terus berkembang di era globalisasi sekarang. Era Global, ditandai oleh berkembangnya IPTEK yang membuat kehidupan manusia terbuka bergaul dengan manusia lain di tempat yang jauh. Era globalisasi juga ditandai ekonomi yang terbuka yang menganut sistem kapitalisme yang juga membawa manusia menghumbar libido seknya. Pendidikan tinggi Islam kini juga di tengah perdagangan internasional termasuk perdagangan antar Negara Asia yang harus direspon oleh pendidikan tinggi Islam agar memproduk lulusan yang berkualitas.Penelitian ini bertujuan menggambarkan  pendidikan tinggi Islam dengan sejarahnya yang cukup yang panjang yang lahir sejak era kemerdekaan, hanya saja perannya belum optimal di tengah bangsa ini, dengan berbagai potensi yang dimilikinya pendidikan tinggi menyiapkan sumber daya manusia di semua bidang kehidupan, tidak mustahil pula akan menjadi bagian dari bangsa ini membawa Indonesai menuju ke peradabannya. Seperti peradaban keemasan Islam yang pernah lahir beberapa abad yang lalu di era Bani Umayyah dan Abbasiyah.